Далекий мой, единственный: [роман] / Татьяна Алюшина - Алюшина Татьяна Александровна (Еще раз про любовь, 2016)
Экземпляры: 3 (20170807) / Инвентарный номер: 49634 / Цена: 98.00 / Авт.знак: А 59 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6